The Impact of Globalization on Local Languages and The Preservation of Traditional Cultures - Muhammad Nurahmad (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
This study explores the complex relationship between globalization, local languages, and the preservation of traditional cultures. As globalization accelerates, the dominance of major world languages poses significant challenges to the vitality of local languages, often leading to their decline or extinction. This research employs a mixed-methods approach, combining quantitative data on language usage trends with qualitative interviews from community leaders, linguists, and cultural practitioners. The findings indicate that while globalization facilitates cultural exchange and access to information, it simultaneously threatens linguistic diversity and traditional cultural practices. The study highlights case studies from various regions, illustrating how local communities respond to these challenges through revitalization efforts, language education programs, and cultural initiatives aimed at preserving their heritage. Additionally, the research discusses the role of technology and social media in both promoting and endangering local languages. Ultimately, this study emphasizes the need for a balanced approach that embraces the benefits of globalization while actively safeguarding local languages and traditional cultures, advocating for policies that support linguistic diversity and cultural preservation in an increasingly interconnected world.